Sustainable seismic retrofitting of a RC building using performance based design approach. Issue 3 (3rd July 2017) - Haghpanah, Fardad; Foroughi, Hamid; Behrou, Reza
Abstract: In the past twenty years, sustainable development has become a challenging subject across many scientific fields. With the built environment as the major component of societies, sustainable construction has been the main player in the whole sustainability mentality. To emphasize on the importance of incorporating sustainability in to seismic retrofitting, three different retrofitting methods (base isolation, concrete jacketing, and steel jacketing) are evaluated for a typical 4-story RC school building under the 1994 Northridge earthquake's ground motion. Using Performance Based Design approach, the objective of retrofitting is to make the building perform in the Immediate Occupancy performance level according to FEMA guidelines so that it can be used as a shelter after disasters. Results show that although retrofitting by concrete or steel jacketing can control story drifts to satisfy maximum allowable values, the performance of the building and consequent damages do not meet the desired performance objective. In addition, accounting for economic and human losses, these retrofitting options will not provide a sustainable structure if a strong earthquake happens in the future. On the other hand, not only base isolation meets the desired performance objective, but also it will provide a sustainable retrofitted structure by drastically reducing economic and human losses.